Pengaruh Diferensiasi Produk, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Di Sulaman Indah Mayang Naras Kota Pariaman Utara - Meidona, Syofria; Yanti, Novi; Nusrizky, Asri; syamsurizal, Syamsurizal (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
ABSTRACT Analysis Of The Influence Of Product Difference, Product Quality And Price On Customer Purchase Decisions In Sulaman Indah Mayang, Naras Kota Pariaman Utara The purpose of this study was to measure the analysis of the effect of product differentiation, product quality and price on customer purchasing decisions in Sulaman Indah mayang, Naras Kota Pariaman Utara. The data collection method in this study used a questionnaire. The population in this study were customers of Sulaman Indah Mayang. The sample of this study amounted to 40 people. The questionnaire test consisted of validity test using the Corrected Item Correlation method, reliability test using Cronbach's Alpha method, classical assumption test which included: normality test, multicollinearity test and heteroscedasticity test, and there was an F test (simultaneous), and t test (partial). The analysis technique uses multiple linear regression analysis method. The results show product differentiation, product quality and price have a significant effect on customer purchasing decisions at Sulaman Indah Mayang simultaneously and partially. The regression is Y = 9.189 + 0.153 X1 + 0.343 X2 + 0.252 X3 and the adjusted R Square value is 0.546 which means that product differentiation, product quality and price variables affect customer purchasing decisions by 54.6%, while the remaining 45.4% customer purchasing decisions influenced by other variables outside the regression equation or variables not examined.